On-street visual analysis on Jalan Hang Jebat, Melaka / Zalina Samadi, Dasimah Omar and Rodzyah Mohd Yunus. - Samadi, Zalina; Omar, Dasimah; Mohd Yunus, Rodzyah (Universiti Teknologi MARA Cawangan Selangor, 2018)
Outdoor space in between heritage buildings of heritage streets defines as ‘outdoor living room’. Whether it’s impressively ‘heritage’ or ‘commercially’ character; physical and socio-cultural characteristics of the streets have great influence towards eliciting on-street pedestrian model. The purpose of this study is to determine the relationship between timeframe and density, activity and movement based on the on-street cultural phenomenon. For the purpose of this paper, the presentation unveiled one section of the study which shares the analysis on-street’s aerial-visual data only. Unobtrusive methods were employed through Digital Photography and Closed Circuit Television (CCTV) at Jalan Hang Jebat, Melaka. The objectives of this study are to interpret density, activity and movement analysis.